2019
DOI: 10.1051/bioconf/20191304002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delayed winter pruning on phenology and ripening kinetics of Pinot Noir grapevines

Abstract: Climate change impacts viticulture with even stronger effects on sparkling wines. Innovative cultural practices represent effective short-term solutions. Among these, postponement of winter pruning later than budburst delayed both vegetative and reproductive cycles as well as technological maturity of several varieties from different wine regions. This research aims to assess the impact of delayed winter pruning on grapevine performance as a function of training system. The trial was carried out in a Pinot Noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…However, budburst postponement was quite small and could hardly be effective in protecting the vine from late frost. Nevertheless, a longer interval was obtained in Pinot Noir by pruning the unpruned canes when the shoots on node ten had three unfolded leaves (Gatti et al, 2019). Despite the delay, at harvest, all treatments showed no differences in berry composition, indicating that vines could fill the gap throughout the season; interestingly, in 2016, no phenology differences were observed among treatments by veraison.…”
Section: Discussionmentioning
confidence: 90%
“…However, budburst postponement was quite small and could hardly be effective in protecting the vine from late frost. Nevertheless, a longer interval was obtained in Pinot Noir by pruning the unpruned canes when the shoots on node ten had three unfolded leaves (Gatti et al, 2019). Despite the delay, at harvest, all treatments showed no differences in berry composition, indicating that vines could fill the gap throughout the season; interestingly, in 2016, no phenology differences were observed among treatments by veraison.…”
Section: Discussionmentioning
confidence: 90%
“…The number of tendrils per vine in Alamata wild grapevine grown in Yirgacheffe (17.56 ± 1.60) was the same as Ruby seedless, Sugraone, Concord in Dilla, and Cardinal in Yirgacheffe. On the same trend, several researchers' findings [ 13 , 17 , 18 ] indicated that there was great possibility of selecting a native wild grapevine to produce new grapevines that could be resistant and tolerant to grapevine biotic and abiotic stresses, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Generally, shorter grapevines are recommended in the viticulture and wine industry. This might be due to pruning and training at the right time and in a proper system as a core element to produce high berry yield and make thus wine of good quality [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…To mitigate such effects, different strategies can be carried out. Among the viticultural ones, these include a reduction of bunch exposure to sunlight by means of sprawl trellis systems [9]; late pruning to delay the phenological cycle [10,11]; a reduction of the leaf/fruit ratio to delay the harvest date [12,13]; grapevine irrigation [14]; and the application of sun protectants [15][16][17]. In newly established vineyards, it is recommended that one should use grapevine varieties and clones that stand out for their resistance to high temperatures, drought, and delayed vegetative cycle [4,18].…”
Section: Introductionmentioning
confidence: 99%